Perfectionistic self-presentation and body image mediated by self-compassion - Ferreira Rocha Nunes, Isabela (2025)
This study investigated the relationship between perfectionist self-presentation and body image and the mediating effect of self-compassion. Participated 708 university students from public and private Higher Education Institutions aged between 18 and 40 years old. The following instruments were completed: Perfectionistic Self-Presentation Scale, Self-Compassion Scale - Short Form and Escala de Avaliação da Satisfação com a Imagem Corporal. The results did not identify differences between the groups. The correlations between the variables were significant. The mediating effect of self-compassion between perfectionist self-presentation and satisfaction with body image was confirmed. The findings indicated that promoting self-compassion can reduce the effects of perfectionist self-presentation on satisfaction with body image.